Specific features of obtaining and using electronic evidence in criminal proceedings - I. O. Teslenko (Law and Safety)
The relevance and importance of this research is due to the fact that scientific and technological progress and rapid development of information technology in all spheres of public life have significantly influenced the emergence of new types of criminal offences. Criminals are using computer systems and other portable devices to commit unlawful acts with increasing frequency. Today, many criminal offences are being committed with the help of information technology around the world, ranging from simple online fraud to the threat of a territorial act. Therefore, one of the ways to record (document) such illegal activities effectively is to obtain (collect) electronic evidence by law enforcement agencies in criminal proceedings. In this regard, the key role is played by evidence, which helps to form an evidence base that makes it possible to notify a person of suspicion, send an indictment to the court and make a final court decision on the guilt (innocence) of a person in committing a particular criminal offence. Achievement of this objective undoubtedly necessitates a specific legal procedure for seizure of electronic evidence in criminal proceedings, which is not yet clearly defined in terms of its collection, leading to numerous cases of courts declaring such evidence inadmissible.